Impact of relative humidity on Bacillus probiotic viability during storage in baked products - Jessie Payne; Danielle Bellmer; Ravi Jadeja; Sarah Spring; Bailey Holcomb; Brooke Holt (Applied Food Research)
Exploring the stability of Bacillus spores is critical because at least 6 CFU/g are needed to confer health benefits when consumed. This study examined how relative humidity (RH) affects the viability of spores from four probiotic strains (L. acidophilus, B. subtilis 1, ProSilienceTM HU58TM, and B. coagulans) in baked food products. The probiotics were tested under three relative humidity (RH) conditions: room indoor RH (ranging from 10% to 75%), 45% RH, and 75% RH, within cookies and crackers over a 12-month storage period. The results showed that both B. subtilis strains maintained the highest viability, with ≤ 2 log reductions over the 12 months. In contrast, B. coagulans experienced ≥ 3.96 log reductions, and L. acidophilus had the lowest survivability, with ≥ 4.5 log reductions in both types of baked goods. Notably, L. acidophilus and B. coagulans fell below the 6 logs (CFU/g) threshold required to deliver health benefits. Among these, only B. coagulans was significantly affected by changes in relative humidity (RH). These findings provide valuable insights into the potential for incorporating Bacillus spores into baked food products and underscore the need to consider storage conditions carefully.